Finds from Kolotov Buerak and Konstantinovskoe settlements - L.F. Nedashkovsky; M.B. Shigapov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
Objects from the small settlements Kolotov Buerak and Konstantinovskoe of the second half of the 13th – 14th centuries situated in the periphery of the Golden Horde city Ukek in the Saratov area of the Saratov region and studied by the expedition organized in 1996-1997, 2002, and 2006 by the Kazan University under the supervision of L.F. Nedashkovsky are considered in the paper. Wearing-apparel components are represented by a bead. Clothes details are a bronze button and a little bell. A rivet of a copper vessel, small lock, coupling of a knife, nails, and a splash of metal are also described. The summarized data on the mass archaeological material, including pottery wares found in the territory of the settlements and represented by a ball, spindle whorls, including the ones made from walls of ceramic vessels, as well as Golden Horde, Old-Russian, Mordvin wares and fragments of the Trebizond amphorae and kashi vessels are provided. The material cultures of the Kolotov Buerak and Konstantinovskoe settlements are similar and can be characterized as inherent to the small rural settlements: the concentration of finds made in their territories is quite low if compared to larger monuments. In the case of the Kolotov Buerak and Konstantinovskoe settlements, we deal with the material culture of the small village and hamlet, respectively. Interestingly, Mordvin pottery and Trebizond amphorae were not found during the excavations at the Konstantinovskoe settlement, in contrast to the Kolotov Buerak settlement. At the Kolotov Buerak settlement, a splash of tin bronze, which confirms that non-ferrous metals were processed at the settlement, and coins absent at the Konstantinovskoe settlement were found.